Living wage', class conflict and ethnic strife - Indraneel Dasgupta (Institute for the Study of Labor (IZA), 2008)
We examine how group-specific differences in reservation wage, arising due to asymmetries in social entitlements, impact on distribution via the joint determination of class conflict between workers and employers, and 'ethnic' conflict among workers. We model a two-dimensional contest, where two unions, representing different sections of workers, jointly but non-cooperatively invest resources against employers in enforcing an exogenously given rent, while also contesting one another. The rent arises from a 'living' wage, set above reservation wage rates via labour regulations. We show that high reservation wage workers gain, and employers lose, from better social entitlements for low reservation wage workers. The latter however benefit, with employers and against the former, from weak labour regulations. When minority/immigrant workers are marginalized both in the labour market and in non-wage entitlements, improving job access and expanding 'social support' has contradictory effects on class and ethnic conflicts. 'Trade unionism', i.e. political articulation of shared economic interests alone, appears insufficient to temper ethnic conflicts among workers.
urn:nbn:de:101:1-20080820161
Keywords: D31; 330; Class conflict; ethnic conflict; living wage; labour regulation; social entitlement; affirmative action; Distribution; Lohndifferenzierung; Anspruchslohn; Betrieblicher Konflikt; Ethnische Gruppe; Arbeitskonflikt; Gewerkschaft; Klassenkampf; Theorie